Bilateral Differences in Dancers' Dynamic Postural Stability during Jump Landings. Issue 4 (December 2020) - Clarke, Frances; Koutedakis, Yiannis; Wilson, Margaret; Wyon, Matthew
Although traditional dance training aims to train dancers' legs equally, the recognized practice of predominately starting and repeating exercises on one side more than the other has led to suggestions that technique classes may cause lateral bias. Such an imbalance could lead to a greater risk of injury; however, despite this potential risk, little is known about the effects of bilateral differences on dancers' postural stability during jump landings, a key dynamic action in dance. Therefore, the aim of this study was to examine the effects of possible bilateral differences on dynamic postural stability during single-leg landing using a time-to-stabilization protocol. Thirty-two injury-free female university undergraduate dancers (19 ± 1.9 years; 164.8 ± 6.7 cm; 62.6 ± 13.6 kg) volunteered for the study. They completed a two-foot to one-foot jump over a bar onto a force platform while stabilizing as quickly as possible. The landing leg was randomly assigned, and participants completed three trials for each leg. No significant differences in dynamic postural stability between right and left legs were revealed, and poor effect size was noted (p > 0.05): MLSI: t = -.04, df = 190, p = 0.940 (CI = -.04, .04, r 2 = 0); APSI: t = .65, df = 190, p = 0.519 (CI = -.06-, .12, r 2 = .09); VSI: t = 1.85, df = 190, p = 0.066 (CI = -.02, .68, r 2 = .27); DPSI: t = 1.88, df = 190, p = 0.061 (CI = -.02, .70, r 2 = .27). The results of this study do not support the notion that dance training may cause lateral bias with its associated risk of injury. Furthermore, dancers' self-perceptions of leg dominance did not correlate with their ability to balance in single-leg landings or to absorb the ground reaction forces often associated with injury. Even when biased training exists, it may not have detrimental effects on the dancer's postural stability.